Physical activity, musculoskeletal disorders, burnout, and work engagement: a cross-sectional study on Italian white-collar employees - Amatori, Stefano; Gobbi, Erica; Sisti, Davide; Pivato, Giorgia; Giombini, Germana; Rombaldoni, Rosalba; Calcagnini, Giorgio; Rocchi, Marco B. L.; Perroni, Fabrizio (Frontiers in Public Health, 2024)
Both mental and physical health of office workers had a positive relationship with their work engagement, with the latter relationship being driven by the association of a healthy diet and physical activity (PA). This observational study aimed to investigate the associations between PA levels, musculoskeletal disorders (MSDs), burnout, and work engagement, in a sample of white-collar employees. A total of 615 workers (age 42.2±9.5 years) successfully completed an online questionnaire comprising work-related information and standardized questionnaires on PA, MSDs, burnout and work engagement. 36.9% of the participants did not meet the PA guidelines, 19.0% adhered to them, and 44.1% exceeded them. A significant portion of participants reported suffering from MSDs, primarily neck/shoulder and/or low back/hip pain. Those exceeding PA guidelines had fewer MSDs compared to non-compliant participants and exhibited better mental health and work engagement. Compliance with PA guidelines was associated with a 38% reduced risk of emotional exhaustion, with an even greater reduction of 47% among those surpassing the guidelines. PA could exert a positive effect on physical and mental health of employees, but only if performed above a certain amount. The study supports the need to identify workplaces as suitable for health-focused interventions and lifestyle changes.